Impregnação de cateteres de Foley com clorpromazina para inibição de biofilmes de bactérias e de leveduras uropatogênicas - Amando, Bruno Rocha (2023)
Urinary tract infection is one of the most common causes of infection in the general population, both in the community and in the hospital environment. The use of indwelling catheters in hospitalized patients makes this type of infection a global public health problem, responsible for about 40% of Healthcare-associated Infections (HAIs) worldwide. Catheter-associated urinary tract infections are directly linked to biofilm formation on these devices. Medical devices impregnated with compounds with antibiofilm activity may be promising prevention strategies against uropathogens. Chlorpromazine (CPZ), an antipsychotic that has antimicrobial action already reported in the literature, in addition to acting as an efflux pump inhibitor, has antibiofilm activity. Thus, the objective of this study was to evaluate the in vitro effect of chlorpromazine impregnated in catheters on the formation of biofilms by Gram-negative bacilli and Candida spp. associated with urinary tract infection. 28 isolates were selected, 13 Gram-negative bacilli and 15 Candida spp. The isolates were evaluated for sensitivity to chlorpromazine, in planktonic and sessile forms. In parallel, the catheter fragments were impregnated at different concentrations, 200 μg/mL, 400 μg/mL and 600 μg/mL for tests with Gram-negative bacilli and 400 μg/mL for tests with Candida spp.. After that, the action of chlorpromazine on the formation of biofilms in these catheter fragments was evaluated by means of the Colony Forming Unit (CFU)/mL count and by confocal microscopy. In addition, the effect of antimicrobials, meropenem and ciprofloxacin against Gram-negative bacilli and fluconazole and caspofungin against Candida spp. was evaluated against biofilms grown on catheters impregnated or not with chlorpromazine. Chlorpromazine showed MICs between 9.76 and 625 μg/mL for bacteria and MICs between 9.76 and 39.06 μg/mL for Candida spp. CPZ was able to inhibit the formation of biofilms, in vitro, of all studied species. All concentrations of chlorpromazine impregnated in catheter fragments inhibited the formation of biofilms, as demonstrated by CFU counts and confocal microscopy. The concentration of 400 μg/mL showed the greatest inhibition of biofilm formation in impregnated fragments. Meropenem was the only antimicrobial in the study that acted synergistically with chlorpromazine on Gram-negative bacillus biofilms grown in impregnated catheters. Thus, it can be concluded that chlorpromazine at a concentration of 400 μg/mL impregnated in fragments of catheters inhibits the formation of biofilms by uropathogens, representing a potential strategy for preventing urinary tract infections associated with the use of medical devices.